If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -4 + -5y + 1 = 0 Reorder the terms: -4 + 1 + 9y + -5y = 0 Combine like terms: -4 + 1 = -3 -3 + 9y + -5y = 0 Combine like terms: 9y + -5y = 4y -3 + 4y = 0 Solving -3 + 4y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 4y = 0 + 3 4y = 0 + 3 Combine like terms: 0 + 3 = 3 4y = 3 Divide each side by '4'. y = 0.75 Simplifying y = 0.75
| -3n(n-3)+4(n+4)= | | 4m+9m=91 | | x-20+153=180 | | ax-b=4c | | -3n(n-3)= | | -5a-4a= | | x^3+7x^2+5x-28=0 | | 5v^2+29v+36=0 | | n3-8=-2 | | x^2-2x-48=X^2 | | a^2-12a-12=0 | | y^2-8y+41=0 | | 4(5-w)/3=-w | | 8z-6z=1 | | 2x^2-2x-48=X^2 | | -2(x-5)=6x+3 | | 2(3z-1)=3(z+2) | | y^2-6y+34=0 | | 8x+2=10x-8 | | 2y+1-17=.5 | | -7-9=2w+2w | | -8=3x-9 | | -4(x+3)=2x-3 | | 3x+96=4(5x+7) | | x+11=2x-5x | | (x^3)-(9x^2)-4=0 | | 5n=-45 | | 126=.7(200+x) | | 15n+22=-7m+18 | | 8x-2x=0 | | 2(4x-3)-8=4x+2x | | 3(z-6)=2z-2 |